2019
DOI: 10.1016/j.jmva.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Tail densities of skew-elliptical distributions

Abstract: Skew-elliptical distributions constitute a large class of multivariate distributions that account for both skewness and a variety of tail properties. This class has simpler representations in terms of densities rather than cumulative distribution functions, and the tail density approach has previously been developed to study tail properties when multivariate densities have more tractable forms. The special skew-elliptical structure allows for derivations of specific forms for the tail densities for those skew-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Consider the input to the hidden unit (S j ) whose PDF f S j (x) is given by (21). The output (K j ) of the hidden unit is given by the non-linear transformation through the activation function ϕ(x) and its mean is given by…”
Section: Appendicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Consider the input to the hidden unit (S j ) whose PDF f S j (x) is given by (21). The output (K j ) of the hidden unit is given by the non-linear transformation through the activation function ϕ(x) and its mean is given by…”
Section: Appendicesmentioning
confidence: 99%
“…On the application side, GSE distributions have been used to model data in various scenarios like in risk theory [19] and Bayesian regression models [20] to name a few. GSE distributions allow flexibility in modelling data with asymmetry and heavy tails [21]. From the wide variety of distributions that belong to the GSE class we choose the SN distribution for the SCME problem at hand for the following reasons: (i) Historically, hardware measurements have shown that the variations in process parameters have been Gaussian in nature.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another useful property that makes multivariate t-distribution and skew t-distribution attractive in financial and actuarial applications is the possibility to take tail dependence between marginals into account. Tail dependence of multivariate tand skew t-distributions has been intensively studied in recent years, see Fung and Seneta [15] or Joe and Li [16], for example. In Kollo et al [17] it is shown that the upper tail dependence coefficient of the skew t-distribution can be several times bigger than the corresponding value of multivariate t-distribution.…”
Section: Introductionmentioning
confidence: 99%